Low Streamflow Analysis in Yeşilırmak Basin - Sümeyye Özkan; Turgay Partal (Doğal Afetler ve Çevre Dergisi)
Drought is generally defined as precipitation that drops significantly below recorded normal levels, negatively affecting soil and water resources in a region. Daily low flow indices are usually used for drought analysis. In this study, 7 and 30-day flow data consisting of daily data of flow observation stations at Kale, Sütlüce, Gömeleönü, Artova and Alpudereköyü stations in Yeşilırmak basin, numbered E14A002, E14A014, E14A018, D14A062 and D14A106, were used. By using 31 years of data, flow rate continuous graphs were drawn first, and low flows were determined by reading Q90, Q95, and Q99 flow rates over these graphs. Then, recurrent flow rates of 2, 5, 10, 25, 50, and 100 years were estimated for 7-day and 30-day low flows. Normal, Lognormal, and Gumbel probability distributions, which are frequently examined in the literature at low flows, are used. The Kolmogorov-Smirnov test was performed to determine the optimal probability distribution. All distributions tested at the 90% and 95% statistical significance levels. Finally, the data were included in the Mann-Kendall and Spearman’s Rho trend analysis, and a significant decrease was observed at the Sütlüce and Artova stations for seven days of minimum flow.